The importance of prenatal diagnosis for the surgical strategy of giant cystic meconium peritonitis: A case report. Issue 1 (January 2023) - Gunadi,; Prathana, Saskia; Amadeus, Verrell Christopher; Ramadhita,; Iskandar, Kristy; Anggraini, Alifah
Abstract: Background: Giant cystic meconium peritonitis (MP) is a relatively rare entity. Prompt surgical treatment is required to manage the underlying etiology and reestablish the continuity of the intestines. Despite perinatal and postoperative care improvements, the overall mortality rate is still relatively high. We reported a giant cystic MP that was recognized using antenatal sonography (US). It was successfully treated with primary anastomosis. Case presentation: We presented a female newborn with a chief complaint of abdominal mass. The prenatal sonography showed an intraabdominal cyst at the 28th week of gestation. She was born at the gestational age of 38 weeks via vaginal delivery from a primigravid mother without complications, with a birth weight of 3275 g. Elective surgery was performed at the age of eight days, and a calcified 10 cm cyst was revealed along with severe adhesions. The cyst was found to communicate with the ileum located 30 cm proximal from the ileocecal junction. No malrotation and volvulus were found. The cyst and a portion of the ileum were resected, followed by a primary end-to-end anastomosis. Pathologic examination showed necrotic tissue lined with epithelial tissue with microcalcifications containing bilirubin pigments, consistent with cystic MP. The patient has uneventfully discharged on postoperative day 17. The patient has normal growth and development, except for delayed walking, at the last follow-up of two years of age. Conclusion: Giant cystic MP is a rare disorder that can be detected early using the antenatal US. Our case highlights the importance of early diagnosis for giant cystic MP using the antenatal US leads to prompt surgical treatment and a more favorable prognosis.